Project-Based Learning Model in Improving Student’s writing skills in the Department of Arabic Language Education in Higher Education - Muid, Abdul; Pratama, Firman Afrian (Universitas Yudharta Pasuruan, 2024)
This study aims to optimize students' ability to write Arabic sentences through a project-based learning model in the Mabadi 'al-Insha' course. This study uses a qualitative method. The study subjects were students in the second semester of the Arabic Language Education Study Program from PBA 1 and PBA 2 classes. Data were collected through tests, observations, and interviews with performance instruments, observation guidelines, and interview guidelines. The data collected from the results of this study will be analyzed using qualitative data analysis. The results showed: 1) The application of the project-based learning model to al-quantity material was carried out in several stages, ranging from determining the theme of writing, determining sources, collecting material (writing rules) and mufradat (vocabulary), composing sentences and discussing them collaboratively with team members, to presentations in front of other teams. 2) Students can generally create sentences based on the elements of sentences that have been learned. For example, making sentences in the form of al-Jumlah Ismiyah consisting of mubtada' and khabar, al-Jumlah al-Fi'liyah consisting of fi'il, fa'il, and maf'ul using sentences that correspond to the attached image and also being able to write with the correct writing and harakat. Based on the study results, the project-based learning model can improve student achievement in writing skills.